Status and direction of arid legumes research in India - Kumar, D (The Indian Journal of Agricultural Sciences, 2005)
Arid legumes are recognized for taming droughts, sustaining soil health and diversifying agriculture and for providing organic food, feed and variety of products of industrial use of export value. Considerable research results have been generated at various levels for making them more productive. In moth bean [Vigna aconitifolia(Jacq) Marechal], varieties maturing in 58-60 (’FMM 96’), 61-64 (’RMO 40’, ’RMO 225’, ’CAZRI Moth 3’), 65-67 (’CAZRI Moth 2’; and 70- 75 (’CAZRI Moth 3’, ’Jawala’, ’IPCMO 880’) days having erect, semi-erect and semi-spreading types, respectively, compared with traditional types maturing in 90-100 days with spreading behaviour, have been developed. These varieties, suited to various rainfall situation of 150-500 mm, are highly productive (500-800 kg/ha) with tendency to escape yellow mosaic virus and drought. In horsegram [Macrotyloma uniflorum (Lam.) Verd.] also, varieties maturing in 80-85 days (’AK 2 1 ’, ’AK 42’) compared with traditional ones maturing in 100-110 days have been developed. Promising varieties in clusterbean or guar. [Cyamopisis tetragonoloba (L.) Taubert] (’RGC 986’, ’RGC 1003’, ’RGC 1002’, ’RGC 1017’, ’RGM 112’) and in cowpea [Vigina unguiculata (L.) Walp,] (’GC 3’, V 585’, ’V 240’, ’RC 101’, ’CoVu 702’) have been developcd, showing improved grain yield and field tolerance to important diseases. Large number of varieties available in active seed chain (35-40) owe their origin from germplasm collected from various situations. Promising donor of diseases and insect-pests are available in cowpea. Workable indices of practical significance for drought tolerance have been provided in moth bean and cowpea. Genetical studies revealed preponderance of both additive and non-additive gene effects for important yield traits and grain yield, however quality traits are less complex. Clusterbean or guar-wheat (Triticum aestivum L.emend. Fiori & Paol.) or guar-Indian mustard [Brassica juncea (L.) Czernj. & Cosson] sequences, proved quite profitable in north India. In southern states, growing short-duration horsegram with rice (Oryza sativa L.) by replacing cowpea is useful and in Orissa horsegram is successfully taken after rice or maize or sorghum [Sorghum bicolor (L.) Moench] crops. Beneficial effects of intercropping clusterbean with pearlmillet [Pennisetum glaucum (L.) R, Br, emend. Stuntz] sorghum, maize and castor (Ricinus communis L.) have been observed at various places. Intercropping 1 or 2 rows of cowpea between 2 rows of pigeonpea, maize, pearl millet or sorghum have ensured success of crops without loss to the main crop, Mixing of moth bean and pearl millet seeds (as two-thirds and one-third of recommended dose, respectively) resulted in highest moth bean’equivalent grain yield even under late-sown rainfed conditions of Rajasthan. Moth bean kept weed-free up to 20-25 days after sowing gave satisfactory grain yield, Among chemical weedicides, Basalin @1 kg ai/ha effectively controlled weeds in moth bean and guar. In cowpea Pendemethalin @ 0.75 kg/ha + 1 hand-weeding at 35 days after sowing gave least weed index (18.0), higher grain yield (502 kg/ha) and benefit : cost ratio (1.69) than weeded check. Bacterial leaf blight (Xanthomonas axonopodis pv cyamopsidis Patel), alternaria leaf spot (Alternaria cucumerina var cymamopsidis), anthracnose [Colletotrichum lindemuthianum (Sacc. & Magn.) Bri. & Cav.], dry root rot [Macrophomina phaseolina (Tassi) Goid], powdery mildew [Odiopsis taurica (Lev.) Sain], fusarium wilt (Fusarium oxysporum f sp tracheiphilum), yellow mosaic virus and cowpea yellow mosaic virus are important diseases of arid legumes, causing considerable yield loss (10-95%). Control measures through chemical, organic and biological means have been developed. Among insects, more than 25% yield losses have been observed due to storage beetles or bruchids (Callosobruchus maculatus Fab.). Edible oil treatment (8 ml/kg seed) proved effective up to 150-200 days against storage pests. Pod-borer [Helicoverpa armigera (Hubner)] is another main pest damaging cowpea and horsegram. Spray of 0.07% endosulphan @ 700 litres/ha has been effective to check the same. Galactomannan guar gum, a polysaccharide compound, is used in a number of industries where water is an important factor, Cluster bean varieties with higher gum content (&gt 32%) and high viscosity (4000-5000 mps.a) are preferred for export. Clusterbean meal obtained from seed coat and germ cell is important feed of monogastric animals and has high proportion of protein content (45-50%). Cowpea and moth bean varieties having almost 27 and 25-26% grain protein are available, whereas horsegram varieties may contain even up to 30% crude protein.